2010
DOI: 10.1016/j.brainres.2010.04.073
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the HMGCR promoter affects transcriptional activity but not the risk for Alzheimer disease in Swedish populations

Abstract: Pages: 25 Pages including 2 tables Abstract:2 Variations in genes associated with cholesterol homeostasis have been reported to modify the risk of developing Alzheimer disease (AD). To date there have been few investigations into variations in genes directly involved in cholesterol biosynthesis and AD. We investigated the influence of the -911C>A polymorphism (rs3761740) in the hydroxy-methyl-glutaryl CoA reductase (HMGCR) gene promoter on basal and regulated transcription, plasma cholesterol levels and the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
1
12
1
2
Order By: Relevance
“…Corroborating this conclusion, the protective HMGCR’s G negative polymorphism was shown to modulate APOE4 risk in cognitively intact and MCI subjects and, to delay age of onset of AD by 3.6 years. These findings are consistent, at least in part, with a recent small case-control study which reported an interaction between the rs3761740 A allele in the promoter region of the HMGCR gene, the APOE E4 allele and an altered risk of AD (OR = 2.41; 95% CI = 0.93–6.22) ( 60 ). Analysis of the allelic distribution of this promoter variant and the rs3846662 SNP examined in the present study reveals a potent linkage disequilibrium (probability: 0.97) between the two variants in our population isolate from eastern Canada which could very well explain the complementary nature of findings reported by the two research teams (data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…Corroborating this conclusion, the protective HMGCR’s G negative polymorphism was shown to modulate APOE4 risk in cognitively intact and MCI subjects and, to delay age of onset of AD by 3.6 years. These findings are consistent, at least in part, with a recent small case-control study which reported an interaction between the rs3761740 A allele in the promoter region of the HMGCR gene, the APOE E4 allele and an altered risk of AD (OR = 2.41; 95% CI = 0.93–6.22) ( 60 ). Analysis of the allelic distribution of this promoter variant and the rs3846662 SNP examined in the present study reveals a potent linkage disequilibrium (probability: 0.97) between the two variants in our population isolate from eastern Canada which could very well explain the complementary nature of findings reported by the two research teams (data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…Keller et al identified a sterol regulatory element (SRE) in this position. They found that the minor A allele was more responsive to the overexpression of sterol regulatory element-binding protein 2, compared with the major C allele [33]. In our experiments, this promoter SNP, which is close to the transcription start of exon 1b, did not contribute significantly to the proximal promoter activity or mRNA level of HMGCR-1b or to the transcription of the canonical HMGCR-1a variant upon sterol depletion.…”
Section: Discussioncontrasting
confidence: 48%
“…Based on these results, the increased HMGCR-1b mRNA level due to sterol depletion in HepG2 cells most likely results from post-transcriptional regulation and/or regulatory promoter DNA sequences not captured in our reporter vector constructs. Moreover, previous studies have identified a functional C > A SNP (rs3761740) in the HMGCR promoter [23,33]. Keller et al identified a sterol regulatory element (SRE) in this position.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for epistasis for rs3846662 has previously been demonstrated: rs3846662 interacts with one locus in hepatic lipase (LIPC) to modulate HDL-C levels [49], and rs3846662 modulates Alzheimer's disease risk in women only [32], a finding suggesting an epistatic interaction between HMGCR and genotype defined by the X and Y chromosomes [50]. Of note, Keller et al [51] recently highlighted an association between a polymorphism within the HMGCR promoter, rs3761740, and transcriptional activity by SREBP. Yet, we previously confirmed that this polymorphism was in linkage disequilibrium with rs3846662 (linkage disequilibrium 0.97) [32].…”
Section: Discussionmentioning
confidence: 96%